2016
DOI: 10.3390/molecules21070887
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Phenolic Compounds Isolated from Adina rubella Leaves Against 5α-Reductase Associated with Benign Prostatic Hypertrophy

Abstract: Adina rubella Hance (AR), a plant native to Korea, has been used as traditional medicine for dysentery, eczema, intoxication, and external hemorrhages. Previous phytochemical studies of AR have reported several components, including terpenoids, phenolics, and alkaloids. The current study evaluated the anti-oxidative and anti-inflammatory activities and 5α-reductase inhibition of isolated compounds of AR leaves to find a potential therapeutic agent for benign prostatic hypertrophy (BPH). Repeated chromatographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…e chemical structures were elucidated by using several types of instrumental analysis. 1Dnuclear magnetic resonance (NMR) experiments, such as 1 H-(600 MHz) and 13 C-(150 MHz) NMR, were performed using an JNM-ECZ600R (JEOL, Massachusetts, USA) at the Center for Research facilities at Chung-Ang University.…”
Section: General Experimentalmentioning
confidence: 99%
See 3 more Smart Citations
“…e chemical structures were elucidated by using several types of instrumental analysis. 1Dnuclear magnetic resonance (NMR) experiments, such as 1 H-(600 MHz) and 13 C-(150 MHz) NMR, were performed using an JNM-ECZ600R (JEOL, Massachusetts, USA) at the Center for Research facilities at Chung-Ang University.…”
Section: General Experimentalmentioning
confidence: 99%
“…e isolated compounds were identified as acanthoside D (1) [16], acanthoside B (2) [17], daucosterol (3) [18], protocatechuic acid (4) [19], chlorogenic acid methyl ester (5) [20], ciwujiatone (6) [21], syringaresinol (7) [22], farnesol (8) [23,24], 3,4-dicaffeoylquinic acid ( 9) [25], and falcarindiol (10) [26] through comparison of their spectral data with the values reported in other studies (Figure 1). Structures of the 10 compounds isolated from FAS were identified by analysis of 1 H and 13 C NMR spectra compared with references. 1 H and 13 C NMR spectra of the compounds (1-10) were included in Supplementary Materials as…”
Section: Isolation and Structural Identification Of The Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme 5α-reductase metabolizes testosterone to DHT, but abnormally high 5α-reductase activity results in excessive DHT production [26]. .It is reported that caffeoyl derivatives from Adina rubella showed good 5α-reductase inhibitory activity [57]. In this experiment, CTL and TI inhibit androgen-induced sebum production by inhibiting the 5α-reductase reaction that produces DHT.…”
Section: Discussionmentioning
confidence: 96%